Analisis Pengukuran dan Verifikasi Kinerja Penghematan Energi Motor Fan Dust Collector Menggunakan VFD dengan Perangkat Lunak RETScreen Expert - Sarwo Turinno; Mochammad Facta; Cahyadi Cahyadi (Universitas Islam Raden Rahmat, Malang, 2024)
In the use of energy in industry, the lack of attention to energy use in meeting load requirements is still a common thing to find. One example is the operation of a dust collector fan motor in the steel industry with maximum capacity continuously at varying process loads, so energy efficiency measures need to be taken. The installation of a Variable Frequency Drive (VFD) to adjust the motor rotational speed according to load requirements is a solution to generate energy savings. This research will evaluate the energy performance of the VFD installation implementation by analyzing energy performance through measurement and verification (M&V) using RETScreen Expert software. From the analysis, the average daily energy consumption before the installation of VFDs was 24,686 kWh/day with energy consumption in one year of 5,924,658 kWh/year. After the installation of the VFD, the average daily energy consumption was 18,018 kWh/day with energy consumption in one year of 4,324,240 kWh/year. With the energy baseline equation, the energy savings generated in one year amounted to 954,747 kWh/year.